DESIGN AND DEVELOPMENT OF ANDROID-BASED TRADITIONAL INDONESIAN CLOTHING IMAGE GUESSING GAME - Nicodemus Rahanra; Dila Erlianti; Rissa Megavitry; Dicky Jhon Anderson Butarbutar; Zulfahmi HB (Informatika, Universitas Jenderal Soedirman, 2023)
In terms of cultural traditions, Indonesia is home to a wide variety of very diverse practices. As a result of different regions of the country, Indonesia is home to diverse cultural traditions. Traditional clothing is an important aspect of the Indonesian culture. The traditions and culture of each region are reflected in the clothes worn at traditional ceremonies; in addition, traditional clothing is a decisive feature of the culture of each region. Concern for the maintenance of national culture, which relates to the wearing of indigenous clothing, has been significantly reduced because of the passage of time. For example, one of the main reasons why people's interest in traditional clothing is not as strong as it used to be is because there is not enough socialization and presentation of Indonesian culture in society. The goal of this study project is to create a learning app for Android based on the guesswork of traditional Indonesian clothing. Research and Development techniques were selected as the proximity used for this investigation. Research and Development As a consequence of this research, an educational game that allows users to predict photos of traditional clothing from Indonesia will be produced on the Android platform. This game will also provide information to players about traditional musical instruments that can be found in Indonesia. It is hoped that educational video games will help in the process of exposing children to pre-existing cultures, and such games can also be seen as offering new perspectives to children. It is possible to draw the conclusion, based on the findings of tests conducted using the black box approach, that this application is capable of functioning in an appropriate way. Moreover, it can provide android smartphone customers with instructional games.